Exploring the Collaboration in Capacity Building between the Nigeria Security and Civil Defence Corps (NSCDC), the International Civil Defence Organisation (ICDO) and the Nigerian Military, 2003–2023 - OLAINA-LADOKUN, Grace Abosede; AKINGA, Anna Yunana; JIBRIN, Hussaini (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
The Nigeria Security and Civil Defence Corps (NSCDC), from 2003 to 2023, enjoyed collaborations in manpower development and capacity building trainings from various national and international institutions, both governmental and non-governmental, such as the International Civil Defence Organisation (ICDO) and the Nigerian Military. The organisation started in Nigeria during the Nigerian Civil War as a volunteer organisation, and has over the years metamorphosed into a full-fledged paramilitary organisation. It works in collaboration with other security outfits to keep national peace and to secure the lives and properties of citizens. Despite the good works of the NSCDC, there is a dearth of scholarly works carried out in the area of its collaborations, training and capacity building. This paper examines some of these collaborations, capacity building cum trainings in man-power development and their importance to the organisation. It examines the sustainability, stability and continuity of these trainings and how to cascade it down to the officers. The findings in this study reveal that there is a generation of officers who got a lot of training and another that does not even know that such opportunities for training exist, a knowledge gap which this paper intends to fill. This study used both quantitative and qualitative research approaches through primary and secondary sources for data collection. The findings in this study reveal the role which training plays in the development of capacity in officers, its challenges and the way forward for the NSCDC.